Cobalt and Zinc Compounds Bearing 1, 10‐Phenanthroline‐5, 6‐dione or 1, 3, 5‐Triaza‐7‐phosphaadamantane Derivatives – Synthesis, Characterization, Cytotoxicity, and Cell Selectivity Studies. Issue 21 (5th June 2013) - Silva, Telma F. S.; Smoleński, Piotr; Martins, Luísa M. D. R. S.; Guedes da Silva, M. Fátima C.; Fernandes, Alexandra R.; Luis, Daniel; Silva, Ana; Santos, Susana; Borralho, Pedro M.; Rodrigues, Cecília M. P.; Pombeiro, Armando J. L.
Abstract: The compounds [mPTA][CoCl4 ] (1, mPTA = N ‐methyl‐1, 3, 5‐triaza‐7‐phosphaadamantane cation), [CoCl(H2 O)(DION)2 ][BF4 ] (2, DION = 1, 10‐phenanthroline‐5, 6‐dione), [Zn(DION)2 ]Cl2 (3 ) and [ZnCl(κ O ‐PTA=O)(DION)][BF4 ] (4 ) were synthesized by reaction of CoCl2 with [mPTA]I or DION and ZnCl2 with DION or 1, 3, 5‐triaza‐7‐phosphaadamantane‐7‐oxide (PTA=O) and DION, respectively. All complexes are water soluble and have been characterized by IR, far‐IR, 1 H, 13 C and 31 P 1 H NMR spectroscopy, ESI‐MS, elemental analyses and single‐crystal X‐ray diffraction structural analysis (for1 ). They were screened against the human tumour cell lines HCT116, HepG2 and MCF7. Complexes2 and3 exhibit the highest in vitro cytotoxicity and show lower cytotoxic activities in normal human fibroblast cell line than in HCT116 tumour cell line, which demonstrates their slight specificity for this type of tumour cell. Abstract : Cobalt and zinc compounds with 1, 3, 5‐triaza‐7‐phosphaadamantane (PTA) derivatives and/or 1, 10‐phenanthroline‐5, 6‐dione (DION) have been synthesized, characterized and screened against several human tumour cell lines. The DION‐containing compounds exhibit specificity for the human fibroblast.